Boston November 10. By His Excellency John Hancock, Esq ; governor of the commonwealth of Massachusetts, A proclamation for a day of thanksgiving : ... Thursday the eleventh day of December next (the day recommended by the Congress to all the states) ... Given at the council-chamber in Boston, the eighth day of November ... one thousand seven hundred and eighty three . ([Printed by Adams and Nourse], 1783)
November 10, 1783 Proclamation by Governor John Hancock setting December 11th as a day of thanksgiving for the cessation of war against Britain, the sovereignty of the United States, and other blessings. Of note, this may be a reprint of the original broadside.